Influence of scale effect and injection speed on morphology and structure of the microinjection molded isotactic polypropylene parts. (12th March 2020) - Wang, Lixia; Jiang, Lin; Li, Shuang; Zhang, Yang; Wang, Dongfang; Li, Qian; Shen, Changyu
Abstract: The morphology and microstructure as well as their forming mechanism of the parts in microinjection molding process are critical. In this work, the coupling effect of scale factor and injection speed on the morphology of the microparts was systematically investigated. Neat isotactic polypropylene parts with thicknesses of 1 mm, 200 μm, and 100 μm were molded at different injection speeds. Polarized light microscope and wide‐angle X‐ray diffraction were used to inspect the microstructures along the sample thickness. In this way, three kinds of typical morphology were observed in the parts, including typical skin‐core structure for the parts with the thickness of 1 mm, noncore shear layer structure for the parts with the thickness of 200 μm, and special skin‐core structure with large fraction of columnar crystal for the parts with the thickness of 100 μm. Most interestingly, it was intuitively and straightforward found that the wall slip occurs when the injection speed exceeds a certain value. Specifically, opposite morphological change trend can be obtained when the parts were molded at different levels of injection speeds. Based on these experimental observations, the formation mechanism was proposed to interpret the morphological evolution. Our work provides a new insight for better understanding the morphology evolution mechanism for microinjection molding parts.